miRNA-Mediated Immune Regulation in Islet Autoimmunity and Type 1 Diabetes - Scherm, Martin G.; Daniel, Carolin (Frontiers in Endocrinology, 2020)
microRNAs have emerged as critical modulators of immune regulation and homeostasis. Their dysregulation is involved in the aberrant differentiation and function of T cell subsets, which results in the onset of islet autoimmunity and the progression to Type 1 Diabetes. Several recent studies have provided considerable insight into the miRNA regulation of immune homeostasis and how dysregulated miRNAs contribute to onset and progression of islet autoimmunity. Specifically, high levels of individual miRNAs impair Treg induction during the onset of islet autoimmunity, thereby driving diseases pathogenesis. The recent advancements in the field suggest that the specific modulation of miRNAs, especially in a T cell-specific manner, could reestablish immune homeostasis and ultimately interfere with the onset of islet autoimmunity.